HUBUNGAN PENGETAHUAN DAN MOTIVASI MAHASISWA INDEKOST TERHADAP TINDAKAN SEKSUAL PRANIKAH DI JALANSEI PADANG KELURAHAN PADANG BULAN SELAYANG I MEDANTAHUN 2013 - intan sabrina; alam bakti; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Problems is teenagers specifically college students shows the increasing symptoms qualitatively and quantitatively, one of which is sexual behaviour. This research intend to know the relationship of boarding students toward premarital sexual behavior which includes the relationship between knowledge and motivation of students boarding againts in Jalan Sei Padang Kelurahan Padang Bulan Selayang I Medan premarital sexual action. This research is a survey research descriptive-analitic. The population in this study were all students aged 18-24 years in both man and women living in the boarding house and rental house in Jalan Sei Padang Kelurahan Padang Bulan Selayang I Medan. The total sample is 61 people, with the sample collecting technique using purposive sampling. The data was collected using a questionnaire as a guide when conducting the interview questions. Based on the research results obtained that there was no correlation (p>0,05) between knowledge, intrinsic motivation toward premarital sexual activity and there was a correlation (p<0,05) between extrinsic motivation toward premarital sexual action. Based on the conclusions is need the suggested for parental guidance in term of religion and moral value instilled within the child, so that children are not compelled to perform deviant behavior especially sexual behavior. The need to provide information and counseling to the manager or owner of the boarding house to be more vigilant and more stringent to provide supervision to students who live in the boarding house where they manage.